2018
DOI: 10.1177/1066896918784669
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus–Positive CD20- and CD45-Negative Diffuse Large B-Cell Lymphoma: A Diagnostic Challenge

Abstract: Diffuse large B-cell lymphoma (DLBCL) is characterized by medium- to large-sized neoplastic cells that express a wide range of B-cell markers including CD19, CD20, CD22, and CD79a. Also, as this is a hematopoietic malignancy, there is expression of the leukocyte common antigen CD45. Lack of CD20 expression occurs in a specific rare heterogeneous subgroup of DLBCL including primary effusion lymphoma, plasmablastic lymphoma, ALK-positive large B-cell lymphoma, and large B-cell lymphoma arising in HHV8+ multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Immunohistochemistry revealed that the atypical cells were markedly positive for the B-cell-specific transcription factors Oct-2 and BOB.1 (Fig. 2b), which confirmed the B-cell derivation of the tumor cells [6]. An extensive analysis of FISH showed the tumor to be negative for C-Myc / IGH translocation as well as translocations involving CCND1 , BCL2 , and BCL-6 .…”
Section: Case Presentationmentioning
confidence: 71%
“…Immunohistochemistry revealed that the atypical cells were markedly positive for the B-cell-specific transcription factors Oct-2 and BOB.1 (Fig. 2b), which confirmed the B-cell derivation of the tumor cells [6]. An extensive analysis of FISH showed the tumor to be negative for C-Myc / IGH translocation as well as translocations involving CCND1 , BCL2 , and BCL-6 .…”
Section: Case Presentationmentioning
confidence: 71%
“… 9 Also, Starr et al described a case of CD20/CD45 negative EBV positive DLBCL but their case was positive for PAX-5 and CD79a while ours was negative for PAX-5. 25 Furthermore, it is still not clear why B-cell markers are downregulated in EBV positive B-cell lymphomas and association of B-cell marker suppression with EBV infection. 20 However, in our patient the serology was EBV and HIV negative as it was EBER in situ hybridisation ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DLBCL is characterized by medium- to large-sized neoplastic cells that express a wide range of B-cell markers including CD19, CD20, CD22, and CD79a. [24] Since CD20-negative DLBCL was reported, [25] several mechanisms for the CD20 phenotypic change after rituximab administration have been proposed, including selection of a CD20-negative clone as a consequence of rituximab exposure or downregulation of the CD20 antigen by genetic and epigenetic changes. [26] As an extremely rare disease, CD20-negative DLBCLs include primary effusion lymphoma (PEL), plasmablastic lymphoma (PBL), anaplastic lymphoma kinase (ALK)-positive DLBCL, and large B-cell lymphoma arising from human herpesvirus 8 (HHV-8)-associated multicentric Castleman disease (MCD).…”
Section: Discussionmentioning
confidence: 99%